A postmodern feminist textual analysis of Jennifer Niven’s “all the bright places” - Leow, Wei Lun (2022)
All the Bright Places is a young adult romance fiction novel by Jennifer Niven published in 2015, about two teenagers, Theodore Finch and Violet Markey, who are both suffering from mental illness and struggle through their own obstacles and expectations from those around them. This study aims to present a textual analysis of All The Bright Places from a postmodern feminist perspective, to determine the portrayal of the male and female protagonists and identify the gender-based literary tropes present in All the Bright Places. The results of this study indicate that the female protagonist is portrayed as weak and fragile at first, reminiscent of the Damsel in Distress trope, but eventually breaks free of her expectations and rediscovers how to live happily. On the other hand, the male protagonist is portrayed as a strong and masculine Knight in Shining Armor at first but ends up committing suicide and becoming a Manic Pixie Dream Boy, a subversion of the Manic Pixie Dream Girl literary trope. Thus, this study concludes that the portrayal of male and female characters in young adult literature as well as the gender-based literary tropes displayed in the novel are influential towards the behaviours and actions of teenagers and young adults, and that the tropes shown in All The Bright Places ultimately act as both a warning and a sign of hope for them in society.